RESISTENSI ANTIBIOTIK DAN DETEKSI GEN PENGODE METHICILLIN RESISTANT Staphylococcus aureus (MRSA) ISOLAT BROILER DI WILAYAH YOGYAKARTA (Resistance of Antibiotics and Detection of Gene Encoding Methicillin Resistant Staphylococcus aureus (MRSA) Isolated from Broiler in Yogyakarta) - Khusnan K; Dwi Kusmanto; Mitra Slipranata (Jurnal Kedokteran Hewan, 2016)
The aims of the research were to evaluate resistance of Staphylococcus aureus against several antibiotics and to detect the gene encoding ofmethicillin resistant Staphylococcus aureus (MRSA) in broiler. Twenty three Staphylococcus aureus isolated from infected broiler in Yogyakartawere used. Genotypic identifications were done based on the occurrence of gene nuc and 23SrRNA. The resistance assay to several antibioticsrevealed that Staphylococcus aureus were resistant to penicillin 78% (18/23), doxycyclin 56% (15/23), gentamicin 26% (6/23), tetracyclin 22% (5/23), erythromycin 13% (3/23), and methicillin 9% (2/23). Detection of gene encoding MRSA on 23 isolats of S. aureus showed that 8 (34.8%) isolates contain gene mecA.Key words: Staphylococcus aureus, broiler, resistant, methicillin, mecA